Microfluidic device enabled quantitative time-lapse microscopic-photography for phenotyping vegetative and reproductive phases in Fusarium virguliforme, which is pathogenic to soybean - Marshall, Jill (Sci Rep, 2017)
Time-lapse microscopic-photography allows in-depth phenotyping of microorganisms. Here we report development of such a system using a microfluidic device, generated from polydimethylsiloxane and glass slide, placed on a motorized stage of a microscope for conducting time-lapse microphotography of multiple observations in 20 channels simultaneously. We have demonstrated the utility of the device in studying growth, germination and sporulation in Fusarium virguliforme that causes sudden death syndrome in soybean. To measure the growth differences, we developed a polyamine oxidase fvpo1 mutant in this fungus that fails to grow in minimal medium containing polyamines as the sole nitrogen source. Using this system, we demonstrated that the conidiospores of the pathogen take an average of five hours to germinate. During sporulation, it takes an average of 10.5 h for a conidiospore to mature and get detached from its conidiophore for the first time. Conidiospores are developed in a single conidiophore one after another. The microfluidic device enabled quantitative time-lapse microphotography reported here should be suitable for screening compounds, peptides, micro-organisms to identify fungitoxic or antimicrobial agents for controlling serious plant pathogens. The device could also be applied in identifying suitable target genes for host-induced gene silencing in pathogens for generating novel disease resistance in crop plants.